Notes on Australasian Orchidaceae 7: Updates on the nomenclature of Sullivania (Diurideae, subtribe Drakaeinae) - Clements, Mark A. (Universidad de Costa Rica, 2021)
Sullivania F.Muell.(Orchidaceae) is recognised as a validly published genus having priority over Paracaleana Blaxell, and thirteen species (eleven described) in Paracaleana are here transferred to it.